LANGUAGE AND IDENTITY - Азимова Севара Абдулла кизи,; Халикова Назира Мухаммаджон кизи, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Language is not just a tool for communication; it is deeply intertwined with both individual and collective identities. The relationship between language and identity is multi-layered, evolving, and culturally significant, encompassing elements of personal self-expression,  social  roles,  and  cultural  belonging.  It  serves  as  a  mirror  to  the experiences,  values,  and  beliefs  of  individuals,  while  also  marking  the  boundaries between  different  groups,  creating  distinctions  based  on  ethnicity,  nationality,  and social class. From a sociolinguistic perspective, language plays a fundamental role in shaping how people view themselves and how they are perceived by others.